THE EFFECT OF LEARNING STRATEGIES AND MOTOR EDUCABILITY ON THE OUTCOMES OF LEARNING BASIC MANIPULATIVE MOVEMENT OF ELEMENTARY SCHOOL STUDENTS - Rahman, Latif Abdul; Subandi, Oman Unju; hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This study aims to determine the effect of the difference between using the Teaching Games for Understanding (TGFU) learning strategy and differentiation learning strategies and motor educability on the learning outcomes of manipulative basic movements in students. The subjects in this study were fourth-grade students of the Integrated Islamic Elementary School (SDIT) Global Insan Madani, Jatirangga, Jatisampurna, Bekasi City, West Java. This study used treatment by level 2 x 2. This study was conducted on 65 selected students. The data analysis technique used was the two-way variance analysis technique (Two-Way Anova) and continued with the Tukey test with a significance level of α = 0.05. The results of this study were (1). The learning outcomes of basic manipulative movements using the Teaching Games for Understanding (TGFU) learning strategy (A1) are higher than those using the differentiation learning strategy (A2); (2). There is an interaction between the learning strategy used (A) and motor educability (B) on the learning outcomes of students' basic manipulative movements; (3). The learning outcomes of basic manipulative movements using the Teaching Games for Understanding (TGFU) learning strategy with high motor educability (A1B1) are higher than using the differentiation learning strategy with high motor educability (A2B1) in grade IV students of SDIT Global Insan Madani; (4). The learning outcomes of basic manipulative movements using the Teaching Games for Understanding (TGFU) learning strategy with low motor educability (A1B2) are higher than using the differentiation learning strategy with low motor educability (A2B2) in grade IV students of SDIT Global Insan Madani.